Биологические аспекты импульсного воздействия радиационного фактора военного характера - Чернявский, Игорь Юрьевич; Марущенко, Владимир Васильевич; Гайдабука, В. Е.; Писарев, Сергей Анатольевич; Меньшов, Сергей Николаевич; Матыкин, Владимир Борисович (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2016)
В рамках НИР по модернизации радиологических принципов войсковой системы радиационной безопасности в работе анализируются медико-радиологические особенности биологического действия импульсного гамма-нейтронного излучения проникающей радиации на различных расстояниях от центра взрыва. Предлагается учитывать пространственно-временное распределения поглощённой дозы путём оценки обобщённого дозиметрического функционала.

As part of the research work for the modernization of military radiological principles of radiation safety, the paper analyzes the medical and radiological features of the biological effect of pulsed gamma-neutron penetrating radiation at different distances from the center of the explosion. It is proposed to take into account the spatiotemporal distribution of absorbed dose by evaluation of the generalized dissymmetric functional.
Biological aspects of impulse exposure of radiation factor which has a military nature
Keywords: поток гамма-нейтронный; радиация проникающая; неравномерность облучения; gamma-neutron flux; penetrating radiation; unevenness of irradiation